A Theoretical Note on the Dealer-Manufacturer Relationship in the Automobile Industry - Koo, Anthony Y. C. (Quarterly Journal of Economics, 1959)
I. Introduction: some terms in automobile pricing, 316. — II. The theoretical basis for conflict of interest — no unique invoice price, 318. — III. Sliding scale vs. flat bonus, 321. — IV. Conclusions, 324.